André de Foix, señor de Asparros: el general que sitió Logroño ( junio de 1521) (Berceo, 2023)
This article goes deeper into the vital trajectory of André de Foix, Lord of Asparros, general in chief of the Franco-Navarrese expedition of 1521. For this purpuse, unpublished documents are used. They come from French and Spanish archives such as the National Library of France, departmental Archive of Atlantic Pyrenees, General and Royal Archive of Navarra and General Archive of Simancas.
Keywords: Array; Array; Array; Array; Array